Witchcraft in Ga-Rankuwa Township: An African Perspective - Mwansa Claude Kimpinde (E-Journal of Humanities, Arts and Social Sciences, 2025)
This study explored the cultural and social significance of witchcraft beliefs and practices in Ga-Rankuwa Township, South Africa, through an African perspective. Utilizing a mixed-methods approach, the research combined academic literature, ethnographic research, and community engagement to provide a comprehensive understanding of witchcraft as a complex phenomenon. The findings revealed that witchcraft operates at the intersection of traditional beliefs, social dynamics, and spiritual worldviews, significantly influencing community interactions and individual behaviours. Discussions highlight how these beliefs shape social relationships, conflict resolution, and coping mechanisms within the community. Based on the insights gained, the study recommends fostering open dialogues within the community to address misconceptions about witchcraft and promote understanding between traditional beliefs and modern perspectives. This research contributes to scholarship by offering a nuanced understanding of witchcraft in contemporary African contexts, emphasizing its relevance in social and cultural dynamics. It also highlights the importance of integrating traditional beliefs into broader discussions on mental health and community well-being, thereby enriching the discourse on spirituality and social cohesion in African societies.